Delayed Postconditioning Protects against Focal Ischemic Brain Injury in Rats - Ren, Chuancheng; Gao, Xuwen; Niu, Gang; Yan, Zhimin; Chen, Xiaoyuan; Zhao, Heng (PloS one, 2008)
We and others have reported that rapid ischemic postconditioning, interrupting early reperfusion after stroke, reduces infarction in rats. However, its extremely short therapeutic time windows, from a few seconds to minutes after reperfusion, may hinder its clinical translation. Thus, in this study we explored if delayed postconditioning, which is conducted a few hours after reperfusion, offers protection against stroke. Focal ischemia was generated by 30 min occlusion of bilateral common carotid artery (CCA) combined with permanent occlusion of middle cerebral artery (MCA); delayed postconditioning was performed by repetitive, brief occlusion and release of the bilateral CCAs, or of the ipsilateral CCA alone. As a result, delayed postconditioning performed at 3h and 6h after stroke robustly reduced infarct size, with the strongest protection achieved by delayed postconditioning with 6 cycles of 15 min occlusion/15 min release of the ipsilateral CCA executed from 6h. We found that this delayed postconditioning provided long-term protection for up to two months by reducing infarction and improving outcomes of the behavioral tests; it also attenuated reduction in 2-[(18)F]-fluoro-2-deoxy-D-glucose (FDG)-uptake therefore improving metabolism, and reduced edema and blood brain barrier leakage. Reperfusion in ischemic stroke patients is usually achieved by tissue plasminogen activator (tPA) application, however, t-PA's side effect may worsen ischemic injury. Thus, we tested whether delayed postconditioning counteracts the exacerbating effect of t-PA. The results showed that delayed postconditioning mitigated the worsening effect of t-PA on infarction. Delayed postconditioning reduced ischemic injury after focal ischemia, which opens a new research avenue for stroke therapy and its underlying protective mechanisms.